PERAN TIGA PILAR DALAM PERUBAHAN SOSIAL MASYARAKAT - Satibi Satibi (LPPM Universitas Bina Bangsa, 2023)
Indonesia is a plural country and a democracy based on Pancasila, a development that accompanies Indonesia's journey as a country of law, continues to experience fluctuating changes based on global social developments, this certainly has an impact on people's lives. The occurrence of changes in each community group, of course, is due to the influence of the development of the community itself, especially the demographic development. Every society is always in the process of social change, in other words, social change is an inherent symptom in every person's life. The changes that occur in society will cause discrepancies between the social elements that exist in society. So that it will change the structure and function of certain social elements of society. To compensate for social changes, it is necessary to present the state through three pillars consisting of Babinsa elements from the Indonesian National Army, Bhabinkamtibmas elements from the National Police of the Republic of Indonesia and ASN (Functional Islamic Extension / Honorary) elements from the Ministry of Religion of the Republic of Indonesia. The purpose of this study is to find out how the role of the three pillars and the efforts made by the three pillars in social change of society. This research uses descriptive qualitative research methods through primary, secondary and tertiary data. The results of this study show that the role of the three pillars in social change of society is very effective and efficient which is carried out jointly both in a structured, incidental and special manner in educating the public. The presence of three pillars that are able to become role models in the midst of society is a conditioner and provides comfort for the community in carrying out their activities. A good three-pillar step, will foster a positive perception of society continuously, this is certainly influenced by the behavior of the three pillars by understanding the value system in society which is closely related to morality, which is packaged and carried out in a structured, incidental and special manner